Idul Fitri Dalam Perspektif Antropologi: Kajian Tentang Mudik, Halal Bihalal, Dan Tradisi Keagamaan Masyarakat Muslim Indonesia - Havid Nur Solikhin; Amri Saputra; Ahmad Arifi (Advances In Education Journal, 2025)
The present study analyzes Eid al-Fitr as a socio-religious phenomenon from the perspective of cultural anthropology by examining the interconnections between rituals, symbols, and social practices that develop within the context of Indonesian Muslim communities. Employing a qualitative approach based on an extensive literature review, this research explores various elements of Eid al-Fitr, including the homecoming tradition (mudik), halal bihalal gatherings, takbir parades, zakat al-fitr, ketupat, new clothing, and the accompanying social dynamics. Thematic analysis is used to identify processes of meaning-making, symbolic representation, social functions, and cultural transformations embedded within the ritual cycle of Eid al-Fitr. The findings reveal that Eid al-Fitr constitutes a “ritual complex” that integrates spiritual, social, and cultural dimensions. Mudik strengthens kinship networks and ancestral identity, halal bihalal functions as a mechanism of social reconciliation, and Eid symbols reinforce moral values, purification, and collective solidarity. Drawing on the theories of Geertz, Turner, and Durkheim, this study demonstrates that Eid al-Fitr is not merely an annual religious observance but also a cultural institution that sustains social cohesion, traditional continuity, and the religious identity of Indonesian Muslims in the midst of social change and modernity.